School participation and children in military families: A scoping review. Issue 3 (3rd July 2018) - Cramm, Heidi; Tam-Seto, Linna
ABSTRACT: Children from military families experience high mobility, stressors due to parental separation and increased risk of parental injury and death. This study aimed to identify and describe school-related occupational disruption for students from military families. Arskey and O'Malley's structured approach to scoping reviews was used. Students in military families experience occupational challenges in managing transitions across schools, maintaining academics, developing social relationships, and engaging in extracurricular activities. The environment can also enable school-related occupations. Occupational therapists are encouraged to consider military-connected students as a vulnerable population and use school-based services to address mental health issues.